The six-sphere framework: A practical tool for assessing monitoring and evaluation systems - Kieron D., Crawley (African Evaluation Journal, 2017)
Successful evaluation capacity development (ECD) at regional, national and institutional levels has been built on a sound understanding of the opportunities and constraints in establishing and sustaining a monitoring and evaluation system. Diagnostics are one of the tools that ECD agents can use to better understand the nature of the ECD environment. Conventional diagnostics have typically focused on issues related to technical capacity and the ‘bridging of the gap’ between evaluation supply and demand. In so doing, they risk overlooking the more subtle organisational and environmental factors that lie outside the conventional diagnostic lens.
Keywords: The six-sphere framework: A practical tool for assessing monitoring and evaluation systems